The Influence of Product Quality and Price Perception on Purchasing Decisions for ELIF - Haryuni, Florentina Triworo (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: Bottled drinking water is a high-consumption daily necessity in Indonesia, reflected in strong household mineral water demand. As a new entrant in the AMDK market, the ELIF brand faces considerable challenges in developing consumer interest and driving purchase decisions. Background Problems: to examine the influence of product quality and price perception on the purchase decision of ELIF bottled water, with purchase interest as a mediating factor, in a case study involving consumers at Rajawali Store, South Jakarta. Novelty: The ELIF brand is worth studying as an emerging local bottled drinking water (AMDK) brand gaining public recognition despite the market dominance of leading brands such as AQUA, LE MINERALE, and CLEO. ELIF applies a differentiation strategy through competitive pricing and a strong commitment to hygienic and safe water quality. Research Methods: This study employed a quantitative approach with purposive, non-probability sampling. The sample size was determined using the Lemeshow formula, resulting in 100 voluntary respondents. Participants were bottled water consumers encountered by the researcher at Rajawali Store and invited to complete a Google Form questionnaire via a shared link. Data were analyzed using SmartPLS 4. Finding/Results: (1) product quality did not affect the purchase interest (2), Price perception has a positive and significant effect on the purchase intention, (3) Product quality has a positive and significant effect on the purchase decision (4) Price perception has a positive and significant effect on the purchase decision, (5) Purchase interest has a positive and significant effect on the purchase decision (6) Product quality does not affect the purchase decision through the purchase interest, (7) Price perception has a positive and significant effect on the purchase decision through the purchase interest. Conclusion: Product quality has no effect on purchase interest. Price perception positively and significantly affects both purchase interest and purchase decision. Product quality and price perception also influence purchase decision directly. Purchase interest significantly influences purchase decision. There is no mediation for product quality, but price perception shows positive mediation through purchase interest.